A practical framework to foster climate action through sport for development and peace - Norrito, Alessio; Todorova, Yvanna (Frontiers in Sports and Active Living, 2025)
The climate crisis necessitates innovative approaches to foster ecological emotions and motivate pro-environmental action, particularly among young people. This conceptual paper explores how the Sport for Development and Peace (SDP) sector can more effectively address this challenge by drawing insights from game design theories. We propose the Mechanics-Dynamics-Aesthetics (MDA) framework, as a heuristic tool for intentionally designing SDP interventions. By starting with desired ecological emotions (Aesthetics), practitioners can shape play-based interactions (Dynamics) through carefully chosen rules and resources (Mechanics). This approach aims to cultivate deeper environmental empathy and encourage climate action by structuring embodied experiences within SDP. We theorize and explain how SDP can be designed to be an imaginative space of learning. In doing so, the paper addresses a significant necessity of implementing SDP initiatives that foster climate action. Finally, we encourage researchers to cross disciplinary boundaries and adopt theoretical imagination in addressing rapidly evolving social challenges.